2022
DOI: 10.1186/s12877-022-02820-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal exposure to the Dutch famine is associated with more self-perceived cognitive problems at 72 years of age

Abstract: Background Undernutrition during critical periods of neurodevelopment can hinder the developing brain with lasting negative consequences for brain size, structure and function. In this study, we describe self-perceived cognitive problems of men and women who were born around the time of the Dutch famine of 1944–45. Methods We compared self-perceived cognitive problems between men and women who had been exposed to the 1944–45 Dutch famine in late, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…We indeed observed more self-perceived cognitive problems in men exposed to famine in early gestation compared with unexposed men in the current study. Although the difference was not statistically significant, the effect size was in line with what we have observed before in a larger sample in the DFBC [ 12 ]. Due to undernutrition, fewer children were conceived during the famine [ 24 , 43 ]; therefore, the number of eligible participants exposed to famine in early gestation was limited.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We indeed observed more self-perceived cognitive problems in men exposed to famine in early gestation compared with unexposed men in the current study. Although the difference was not statistically significant, the effect size was in line with what we have observed before in a larger sample in the DFBC [ 12 ]. Due to undernutrition, fewer children were conceived during the famine [ 24 , 43 ]; therefore, the number of eligible participants exposed to famine in early gestation was limited.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our findings on the Stroop-like task may have been an early sign of accelerated cognitive aging [ 11 ]. Our subsequent findings, that men exposed to famine in early gestation reported more self-perceived cognitive problems at age 72 and more often consulted a healthcare professional for these problems, is in line with this hypothesis, as self-perceived cognitive problems have been associated with (future) cognitive decline and increased dementia risk [ 12 , 13 , 14 , 15 ]. Apart from worse performance on the Stroop-like task and poorer self-perceived cognitive function, we found that men exposed to famine in early gestation had worse brain perfusion, smaller total brain volumes, and increased BrainAGE (an MRI-based measure estimating clinical brain aging).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Author details 1 Department of Epidemiology and Data Science, Amsterdam Public Health Research Institute, Amsterdam UMC, University of Amsterdam, Meibergdreef 9, 1105 AZ Amsterdam, the Netherlands. 2 Department of Obstetrics and Gynaecology, Amsterdam Public Health Research Institute, Amsterdam UMC, University of Amsterdam, Meibergdreef 9, Amsterdam, The Netherlands.…”
Section: Open Accessmentioning
confidence: 99%